The Hungarian reception of Dostoevsky until the 1920s in the context of European and Hungarian Modernism - Dukkon, Ágnes (Slavica, 2024)
This paper deals with the questions Dostoevsky’s reception in Hungary in the late 19th and early 20th centuries. The author investigates the growing interest in Dostoevsky in the context of the new trends of art and literature and gives a detailed survey of the most characteristic reactions (i.e. reviews, studies, introductions to books) about the new translations and editions of Dostoevsky’s works. Among the most relevant questions addressed arestereotypes about Russian culture and people, living in Hungary duringthe past centuries, the various interpretations of Crime and Punishment, and some comparative aspects in the analyses of this novel.